A randomized prospective multicenter trial for stroke prevention by prophylactic surgical closure of the left atrial appendage in patients undergoing bioprosthetic aortic valve surgery--LAA-CLOSURE trial protocol - Kiviniemi Tuomas; Bustamante-Munguira Juan; Olsson Christian; Jeppsson Anders; Halfwerk Frank R.; Hartikainen Juha; Suwalski Piotr; Zindovic Igor; Copa Guillermo Reyes; van Schaagen F.R.N.; Hanke Thorsten; Cebotari Sergei; et al. (MOSBY-ELSEVIER, 2022)
Patients undergoing surgical aortic valve replacement (SAVR) are at high risk for atrial fibrillation (AF) and stroke after surgery. There is an unmet clinical need to improve stroke prevention in this patient population. The LAA-CLOSURE trial aims to assess the efficacy and safety of prophylactic surgical closure of the left atrial appendage for stroke and cardiovascular death prevention in patients undergoing bioprosthetic SAVR. This randomized, open-label, prospective multicenter trial will enroll 1,040 patients at 13 European sites. The primary endpoint is a composite of cardiovascular mortality, stroke and systemic embolism at 5 years. Secondary endpoints include cardiovascular mortality, stroke, systemic embolism, bleed fulfilling academic research consortium (BARC) criteria, hospitalization for decompensated heart failure and health economic evaluation. Sample size is based on 30% risk reduction in time to event analysis of primary endpoint. Prespecified reports include 30-daysafety analysis focusing on AF occurrence and short-term outcomes and interim analyses at 1 and 3 years for primary and secondary outcomes. Additionally, substudies will be performed on the completeness of the closure using transesophageal echocardiography/cardiac computed tomography and long-term ECG recording at one year after the operation. (Am Heart J 2021;237:127-134.)